Choose Wisely: Surgical Selection of Candidates for Outpatient Anterior Cervical Surgery Based on Early Complications Among Inpatients. (19th October 2022) - Carlson, Bayard C.; Dawson, John M.; Beauchamp, Eduardo C.; Mehbod, Amir A.; Mueller, Benjamin; Alcala, Christopher; Mullaney, Kevin J.; Perra, Joseph H.; Pinto, Manuel R.; Schwender, James D.; Shafa, Eiman; Transfeldt, Ensor E.; et al.
Abstract : Background: Anterior cervical discectomy and fusion (ACDF) and cervical disc arthroplasty (CDA) are attractive targets for transition to the outpatient setting. We assessed the prevalence of rapid responses and major complications in the inpatient setting following 1 or 2-level ACDFs and CDAs. We evaluated factors that may place patients at greater risk for a rapid response or a postoperative complication. Methods: This was an institutional review board-approved, retrospective cohort study of adults undergoing 1 or 2-level ACDF or CDA at 1 hospital over a 2-year period (2018 and 2019). Data on patient demographic characteristics, surgical procedures, and comorbidities were collected. Rapid response events were identified by hospital floor staff and involved acute changes in a patient's clinical condition. Complications were events that were life-threatening, required an intervention, or led to delayed hospital discharge. Results: In this study, 1, 040 patients were included: 888 underwent ACDF and 152 underwent CDA. Thirty-six patients (3.5%) experienced a rapid response event; 22% occurred >24 hours after extubation. Patients having a rapid response event had a significantly higher risk of developing a complication (risk ratio, 10; p < 0.01) and had a significantly longer hospital stay. Twenty-four patients (2.3%) experienced acute complications; 71% occurred >6 hours after extubation. Patients with a complication were older and more likely to be current or former smokers, have chronic obstructive pulmonary disease, have asthma, and have an American Society of Anesthesiologists (ASA) score of >2. The length of the surgical procedure was significantly longer in patients who developed a complication. All patients who developed dysphagia had a surgical procedure involving C4-C5 or more cephalad. Patients with a rapid response event or complication were more commonly undergoing revision surgical procedures. Conclusions: Rapid response and complications are uncommon following 1 or 2-level ACDFs or CDAs but portend a longer hospital stay and increased morbidity. Revision surgical procedures place patients at higher risk for rapid responses and complications. Additionally, older patients, patients with chronic obstructive pulmonary disease or asthma, patients who are current or former smokers, and patients who have an ASA score of ≥3 are at increased risk for postoperative complications. Level of Evidence: Prognostic Level III . See Instructions for Authors for a complete description of levels of evidence.